2021
DOI: 10.1007/s12013-021-01003-x
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Phospholipase A2 Enzymes in Acute Lung Injury

Abstract: The secretory phospholipase A 2 (sPLA 2 ) group of secreted enzymes hydrolyze phospholipids and lead to the production of multiple biologically active lipid mediators. sPLA 2 s and their products (e.g., eicosanoids) play a significant role in the pathophysiology of various inflammatory diseases, including life-threatening lung disorders such as acute lung injury (ALI) and the Acute Respiratory Distress Syndrome (ARDS). The ALI/ARDS spectrum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 68 publications
(105 reference statements)
0
18
0
1
Order By: Relevance
“…Activated sPLA2-IIA is an inflammatory agent that is particularly destructive to cell biomembranes due to its ability to hydrolyzed fatty acids [ 73 75 ]. The membrane damage leads to the release of arachidonic acids and lysophospholipids; the arachidonic acids are then metabolized by cyclooxygenase to thromboxanes, prostacyclins, prostaglandins, etc.…”
Section: Melatonin/pla2 Interactionsmentioning
confidence: 99%
“…Activated sPLA2-IIA is an inflammatory agent that is particularly destructive to cell biomembranes due to its ability to hydrolyzed fatty acids [ 73 75 ]. The membrane damage leads to the release of arachidonic acids and lysophospholipids; the arachidonic acids are then metabolized by cyclooxygenase to thromboxanes, prostacyclins, prostaglandins, etc.…”
Section: Melatonin/pla2 Interactionsmentioning
confidence: 99%
“…Prior work by our group and others has also demonstrated that inhibition or genetic deletion of gVPLA 2 attenuates murine ALI induced by LPS or high tidal volume ventilation [28,29,32]. These prior studies provide a strong scientific premise for the important role of gVPLA 2 in ARDS [18]. The current study seeks to characterize the role of gVPLA 2 in mediating lung EC dysfunction and ALI induced by the clinical-relevant pathogen MRSA (USA300 strain).…”
Section: Introductionmentioning
confidence: 90%
“…Flow cytometry was used to sort the mPVEC through the selection of CD31+/CD45-cells [33]. mPVECs (passages [13][14][15][16][17][18][19] were grown in endothelial growth medium-2 (EGM-2) at 37 • C in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into the biological role of mammalian group IIA PLA 2 , also known as inflammatory PLA 2 , in the development of several pathologies of inflammatory and immunological origin have been described. Several studies have revealed that group IIA sPLA 2 s are present in high levels in rheumatoid arthritis [47][48][49][50], acute pancreatitis [51][52][53], septic shock [54,55], Crohn's disease and ulcerative colitis [56][57][58], respiratory distress syndrome [59][60][61], bronchial asthma and allergic rhinitis [59,62], atherosclerosis [63,64], autoimmune diseases [65], and cancer [66][67][68][69]. These observations imply that both local and systemic inflammation are associated with the release of sPLA 2 s in vivo, thus raising the unclear question of the role of these PLA 2 s in inflammatory reactions.…”
Section: Phospholipases Amentioning
confidence: 99%